Authorship in leading management journals: representation from Asian business schools - Kamal, Shawkat; Duc, Le Manch; Qi, Zhu (© 2010 Bangladesh Institute of Management, 2012)
This study investigates the representation of works by authors of affiliated with Asian business schools in top management journals. The results did not indicate strong support for change in the representation of works by such scholars during the study period. Looking at the articles published in the top nine journals in the field of strategic management between the year 1999 and 2006, it was fond that scholars affiliated to Asian business schools having North American educational background were more productive compared to those having educational background were more productive compared to those having educational background from elsewhere. The findings also revealed that these scholars prefer to publish more in North America based journals when compared with European based journals; and having coauthors who are affiliated with North American business schools enhances the possibility of publication in top tier management journals.